Adsorption kinetics and Box–Behnken design optimization for organic dyes on tungsten oxide. Issue 17 (29th July 2022) - Arteaga-Jiménez, A.; Trejo-Pérez, M. G.; García-García, A. L.; González-Jasso, E.; Vidales-Hurtado, M. A.
ABSTRACT: Transition metal oxides have been applied to degrade organic dyes found in water bodies via photocatalysis. To do it, however, is essential that the dye molecules adsorb onto the metal oxide surface. Thus, optimizing the adsorption capacity of the adsorbent increases the probability of reaction between oxidation radicals and organic dye molecules and maximizes the effectiveness per gram of photocatalyst. With this in mind, we studied the adsorption behavior of Methylene Blue (MB) and Acid Orange 7 (AO7), two commonly found pollutants, as a function of dilution's pH, WO3 load, and initial dye concentration. We found out that WO3 adsorbs up to 80% of MB at pH = 6, and 13% of AO7 at pH = 2, although it is unable to adsorb AO7 at the natural pH of the dye dilution. Assuming a pseudo-second order kinetics model for the analysis of the MB adsorption amount, we determined a rate constant k 2  = 6 × 10 −2 (g · mg −1 )/min for the adsorption process. We put forward a molecular model for adsorption, driven by concentration gradients and electrostatic interactions. Finally, from a statistical analysis, we determined that pH is the most significant factor for the adsorption of MB and AO7 on WO3, reinforcing the notion that electrostatic interactions are the main mechanism driving the adsorption process. The Box–Behnken design optimization also evinces the key playing role of WO3 load in the adsorption percentage of AO7 and let us establish the optimal load required to maximize adsorption. GRAPHICAL ABSTRACT: UF0001